In situ Skeletal Growth Rates of the Solitary Cold-Water Coral Tethocyathus endesa From the Chilean Fjord Region - Rossbach, Susann; Rossbach, Felix Ivo; Häussermann, Verena; Försterra, Günter; Laudien, Jürgen (Frontiers in Marine Science, 2021)
Cold-water corals (CWC) can be found throughout a wide range of latitudes (79°N–78°S). Since they lack the photosymbiosis known for most of their tropical counterparts, they may thrive below the euphotic zone. Consequently, their growth predominantly depends on the prevalent environmental conditions, such as general food availability, seawater chemistry, currents, and temperature. Most CWC communities live in regions that will face CaCO3 undersaturation by the end of the century and are thus predicted to be threatened by ocean acidification (OA). This scenario is especially true for species inhabiting the Chilean fjord system, where present-day carbonate water chemistry already reaches values predicted for the end of the century. To understand the effect of the prevailing environmental conditions on the biomineralization of the CWC Tethocyathus endesa, a solitary scleractinian widely distributed in the Chilean Comau Fjord, a 12-month in situ experiment was conducted. The in situ skeletal growth of the test corals was assessed at two sites using the buoyant weight method. Sites were chosen to cover the naturally present carbonate chemistry gradient, with pH levels ranging between 7.90 ± 0.01 (mean ± SD) and 7.70 ± 0.02, and an aragonite saturation (Ωarag) between 1.47 ± 0.03 and 0.98 ± 0.05. The findings of this study provide one of the first in situ growth assessments of a solitary CWC species, with a skeletal mass increase of 46 ± 28 mg per year and individual, at a rate of 0.03 ± 0.02% day. They also indicate that, although the local seawater chemistry can be assumed to be unfavorable for calcification, growth rates of T. endesa are comparable to other cold-water scleractinians in less corrosive waters (e.g., Lophelia pertusa in the Mediterranean Sea).